Pemasangan Jaring Kontrol GNSS untuk Studi Deformasi Sesar Opak Segmen Segoroyoso - Fahrurrazi, Djawahir; Atunggal, Dedi (2014)
Segoroyoso is one of the Opak fault segments. This segment is very interesting to be researched because it is a complex segment that includes the main Opak fault and some micro faults from the west to east direction. This study aims to establish GNSS control networks for ground movement monitoring due to tectonic phenomena beneath the segoroyoso segment of Opak fault and to define the above mentioned GNSS control points on 2013 epoch. The network design was optimized by using the least square method. The GNSS observation was carried out simultaneously in all the control points by using 6 dual frequency GNSS receivers with 8-10 hours of survey duration (each). GNSS data processing was done by using commercial software. This research has successfully established six control points namely SGY1, SGY2, SGY3, TGD2, SGY5, and SGY6. Several different network optimizations have been carried out. This optimization research stage indicates that TGD2 is relatively the best reference point. The control point coordinates for the 2013 epoch have been defined. The GNSS data processing shows consistent results compared to the network design optimization. It is concluded that TGD2 seems to be the most suitable reference control point for the network where the error ellipses of other control points are evenly distributed in spite of the SGY6’s ellipse error is slightly bigger than the other.